(untitled) (Revista de Ciências Agroveterinárias, 2022)
The sunflower is an oilseed species, rustic, cultivated in different agroecosystems. The responses of cultivars to nitrogen fertilization vary according to the cultivar and environment. Therefore, this research aimed to evaluate the response of biometric characters of sunflower cv. Embrapa 122-V2000 under N doses. The experiment was carried out in a randomized block design with five treatments (0, 40, 80, 120 and 160 kg N ha-1) and four blocks. All characters were influenced (p<0.05) by N doses, fitting to the quadratic model. The maximum values of plant height (1.68 m), stem diameter (22.71 mm), leaf area (423.41 cm2), capitulum diameter (15.22 cm), dry biomass yield (6,075.13 kg DM ha-1) and grains (2,982.89 kg ha-1), N use efficiency from biomass (80.3 kg kg-1) and grains (43.27 kg kg-1) close to 90 kg N ha-1, this dose being recommended for the edaphoclimatic conditions of the Agreste Meridional Region of Pernambuco, Brazil.